3(3x-7)+5=2(2x+12)

Simple and best practice solution for 3(3x-7)+5=2(2x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-7)+5=2(2x+12) equation:


Simplifying
3(3x + -7) + 5 = 2(2x + 12)

Reorder the terms:
3(-7 + 3x) + 5 = 2(2x + 12)
(-7 * 3 + 3x * 3) + 5 = 2(2x + 12)
(-21 + 9x) + 5 = 2(2x + 12)

Reorder the terms:
-21 + 5 + 9x = 2(2x + 12)

Combine like terms: -21 + 5 = -16
-16 + 9x = 2(2x + 12)

Reorder the terms:
-16 + 9x = 2(12 + 2x)
-16 + 9x = (12 * 2 + 2x * 2)
-16 + 9x = (24 + 4x)

Solving
-16 + 9x = 24 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-16 + 9x + -4x = 24 + 4x + -4x

Combine like terms: 9x + -4x = 5x
-16 + 5x = 24 + 4x + -4x

Combine like terms: 4x + -4x = 0
-16 + 5x = 24 + 0
-16 + 5x = 24

Add '16' to each side of the equation.
-16 + 16 + 5x = 24 + 16

Combine like terms: -16 + 16 = 0
0 + 5x = 24 + 16
5x = 24 + 16

Combine like terms: 24 + 16 = 40
5x = 40

Divide each side by '5'.
x = 8

Simplifying
x = 8

See similar equations:

| 5y-6-3y+5=0 | | sin9pie/3 | | 81=9x+9 | | 4x-6x+x-4+5x= | | 2/9-31=16=7/9 | | x^2-15x-52=0 | | 9=a/3-4 | | -3b+10(b-4)=-110 | | 8(x+4)-6x=x-2 | | 1-7x-1=-21 | | 5m+10=5m-10 | | -23=-4x-x-8 | | 6.1x-3+x-1.3= | | 29=10n+9 | | 5-8(s+1)=-9s+4 | | 6y-1= | | 0.3x-17=1.1x-25 | | 4/5x-1/5=9 | | 2(x+5)=36 | | 3x(x-2)+(x-2)= | | 3a+5+4a-6=2 | | x^2-10+11=0 | | -5-1.2= | | 2*log*x=log*2+log(3*x-4) | | 10+x-7x=-38 | | 8x+6(1+5x)=2 | | 6.1+1= | | 7+7k=147 | | 2/3m-1/3=5/12 | | 8-3y=2(3+y)-5 | | -2(n-4)=10-2N | | -2y-5+2y^2=0 |

Equations solver categories